The Expansion of the New Autonomous Region of South Garut Regency as an Alternative to Realize the Effectiveness of Public Services - Diki Suherman; Yogi Suprayogi Sugandi; Mohammad Benny Alexandri (Jurnal Manajemen Pelayanan Publik, 2021)
The existence of regional autonomy, one of which is trying to provide the best quality service and helping the welfare of local communities with regional capabilities in managing their own regions. But in reality, regional autonomy does not provide equitable publik services, this is because Garut Regency has a large area and a large population and is not balanced with the capacity and resources of the local government in serving the community. The purpose of this study is to determine the expansion of the New Autonomous Region of South Garut Regency as an alternative to realizing the effectiveness of publik services. The method in this research uses a descriptive qualitative approach, collecting data through interviews. Interactive model of data analysis techniques consisting of data reduction, data presentation and increasing conclusions. The results of this study are the division of South Garut Regency is an appropriate and fast alternative as an effort to provide effective and optimal publik services in overcoming development disparities. The conclusion of this study in terms of speed, the expansion of South Garut Regency can help accelerate the services provided by the local government with the support of adequate human resources and infrastructure. In terms of accuracy it helps in providing services that reach all corners of the village and on targeted budget allocations. In terms of convenience when it makes it easier to serve the community because of the government offices that are close to access that is accessible to the community. In terms of justice, the large population is balanced with the number of government agencies / offices in the South Garut region.